Access to and use of long-lasting insecticidal nets and factors associated with non-use among communities in malaria-endemic areas of Al Hudaydah governorate in the Tihama region, west of Yemen - Samira M. A. Al-Eryani; Mohammed A. K. Mahdy; Abdulsalam M. Al-Mekhlafi; Rashad Abdul-Ghani (Malaria Journal, 2017)
Abstract Background Universal coverage of the targeted malaria-endemic areas with long-lasting insecticidal nets (LLINs) is implemented as one of the key interventions for malaria control and elimination in Yemen. In 2013, through a mass campaign, LLINs were distributed to the targeted communities in Al Hudaydah governorate. This study aimed to assess the ownership of, access to, and use of LLINs. It also aimed to identify factors associated with not using LLINs in malaria-endemic areas of Al Hudaydah in the Tihama region, west of Yemen. Methods A cross-sectional survey was conducted in four districts (Ad Durayhimi, Al Marawi’ah, Al Mansuriyah and Bayt Al Faqiah) in Al Hudaydah during February 2016. A total of 701 households were included in this study. Data on socio-demographic characteristics and availability of LLINs were collected by interview and observation. Four indicators for malaria prevention using LLINs; proportion of households with at least one LLIN, proportion of households with at least one LLIN for every two people, proportion of population with access to LLINs in the surveyed households and proportion of population who slept under LLINs the previous night of the survey were calculated as indicated by Roll Back Malaria Monitoring and Evaluation Reference Group. Use to access ratio was assessed. Factors associated with not using LLINs among people with access were also investigated. Results Of 701 households with 4900 de facto population, ownership of at least one LLIN was 90.6%, while 24.1% owned at least one for every two people during the survey in 2016. The overall proportion of people with access to LLINs was 51.5% (95% CI 50.1–52.9). Only 19.0% (95% CI 17.9–20.1) slept under LLINs the night before the survey and the overall use to access ratio was 0.37. The proportions of children under 5 years of age with access to and use of LLINs were 13.7 and 42.5%, respectively. On the other hand, the proportions of pregnant women with access to and use of LLINs were 16.4 and 20.0%, respectively. ...